Standard daily dosage versus pulse dosage of Isotretinoin in acne vulgaris: A hospital based comparative study - Aryal, Eliz; Shrestha, SB; Pokhrel, G; Bhattarrai, S (Journal of Kathmandu Medical College, 2018)
Background: Acne is a multi factorial disease ranging from a couple of comedones and pustules to severe nodulocystic fulminantacne. Isotretinoin (13-cis-retinoic-acid) drug affect all the factors involved in pathogenesis of acne and approved by Food and Drug Administration in 1982. It causes several dose-dependent mucocutaneous and systemic side effects and cost effectObjective: To assess and compare the efficacy and tolerability of two regimens (daily conventional and pulse dose) in moderate to severe acne vulgaris.Methodology: This is a prospective randomized comparative study in moderate to severe acne vulgaris in Kathmandu Medical College Teaching Hospital. The patients were randomly divided into two groups (A and B). In group A conventional dose of 20 mg of oral isotretinoin was given daily and in group B 20 mg of oral isotretinoin was given thrice (Pulse Dosage in alternate day) in a week for six months. The baseline haematological, biochemical and radiological (lumbosacral spine) was compare on first, third and six month.Results: Seventy-four patients were enrolled with mean age of 21.73 years. Patients with daily regimen show good response throughout the therapy for six months (1st, 3rd 6th months), where as those in pulse therapy show moderate to poor response during early month and gradually improve by end of sixth month. At end of sixth month, both the regimen show good response and was statistically significant.Conclusion: However, the pulse dose regimen makes the treatment more acceptable, for patients with acne than the classical standard daily regimen, in term of side effects and cost effectiveness and patient compliance. Journal of Kathmandu Medical CollegeVol. 7, No. 2, Issue 24, Apr.-Jun., 2018, Page: 68-74